Knowledge and Understanding of Personal Income Tax Payments among Residents of Lat Lum Kaeo District, Pathum Thani Province - มะดิเยาะ, นราวาตี; แสงแก้ว, พรทิพย์; มะดิเยาะ, อะวาฎิบ; อาดำ, อาทิตยา; เกิดกำไร, ธราดล (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to examine and compare the level of knowledge and understanding of personal income tax payment among residents in Lat Lum Kaeo District, Pathum Thani Province. The study focused on four aspects: general knowledge of personal income tax, expense deductions and tax allowances, tax filing, and awareness and understanding of tax measures and related laws. The comparisons were conducted based on age, occupation, educational level, and income level. This study employed a quantitative research design. A sample of 396 residents was selected using simple random sampling. Data were collected through questionnaires. Statistical analyses included percentage, mean, standard deviation, F-test, and pairwise comparisons using Scheffe’s method.           The findings revealed that, overall, residents in Lat Lum Kaeo District, Pathum Thani Province demonstrated a high level of knowledge and understanding of personal income tax payment. Among the four aspects, general knowledge of personal income tax ranked highest, followed by tax filing, expense deductions and allowances, and awareness and understanding of tax measures and related laws, respectively. Furthermore, the comparative analysis indicated that residents with different ages, occupations, educational levels, and income levels exhibited significantly different levels of knowledge and understanding of personal income tax payment, both overall and in each aspect, at the .01 level of statistical significance.